Improving The English Skills Of Elementary School Students Using The Phonetic Method - Dewi Lestari (Prosiding University Research Colloquium, 2021)
This research was conducted using a qualitative descriptive method. The study aims toknow the effectiveness of phonetic methods in improving the English skills of elementaryschool students. Language plays a very important role in our daily lives, to communicateideas to others. Language skils are the basic ingredients for everyone to expressthemselves starting from the feelings, desires, opinions, and needs of each individual.The more language a person knows, the easier it is for him to communicate.Understanding English must be solidified to students as an international language. Thestudy was based in the thought that students should be speaking English in dailyinteractions in the school language program. Because of this, the need to learningpronunciation, vocabulary and grammar in English learning is essential for improvingstudents language skills, students should study the pronunciation, vocabulary, andgrammar as much as possible to establish good communication with other students.